Relasi Agama dengan Negara dalam Pemikiran Islam: Studi atas Konteks Keindonesiaan - La Ode Ismail Ahmad (Millah: Journal of Religious Studies, 2011)
The relationship between religion and the state becomes a crucial issue among scholars. On the one hand, there is no relationship between religion and state, and vice versa religion and state has no significant relationship. This issue is being debated for the Islamic community itself, because there is no teks that requires forming in Islamic countries, thus opening the door of ijtihad. Indonesia, as the world’s largest Muslim countr y Indonesia does not need to be demanding an Islamic state, what matters is the substance and essence-its essence, not a very formal form symbolists. Pancasila as the state problem is formulated by the leaders of Indonesia which largely Muslim. Basically, Pancasila not contradictory, but inline with Islam. Even the precepts of Pancasila depend on it are the basic teachings of Islam.